2021
DOI: 10.3390/pathophysiology28030027
|View full text |Cite
|
Sign up to set email alerts
|

Proton Quantum Tunneling: Influence and Relevance to Acidosis-Induced Cardiac Arrhythmias/Cardiac Arrest

Abstract: Acidosis and its associated pathologies predispose patients to develop cardiac arrhythmias and even cardiac arrest. These arrhythmias are assumed to be the result of membrane depolarization, however, the exact mechanism of depolarization during acidosis is not well defined. In our study, the model of quantum tunneling of protons is used to explain the membrane depolarization that occurs during acidosis. It is found that protons can tunnel through closed activation and inactivation gates of voltage-gated sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…These end goals of these Quantum Communication sessions will be delivered to the boundary solution in a five-dimensional Chern-Simons supergravity application layer. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] In this effort, I propose QFT to QM Maximally Entangled States to achieve very high accuracy levels as say of the position and momentum, and spin and polarization projections which are represented in this Quantum Homeopathy paradigm, by Hermitian operators for the generation of Quantum Hormetic designed molecules of the Roccustyrna_gs, the Roccustyrna_fr, the Roccustyrna_gs_consv, and the Gissitorviffirna_TM ligands. The biological essence of this scheme is illustrated here by Quantum formalization of Quantum fields Theory (QFT) Uncertainities and Topology Geometric Methods in a Functional Quantum Negative Space for FH0∆ holomorphic functions for the generation of novel drug designs and theirs generalized k-nearest neighbors within this Quantum Homeopathy computing chemical context targeted in a atomistic level the (S) Spike proteins and its aspartic acid (SD614) and glycine (SG614) protein apparatus.…”
Section: Divide-and-conquer Approach For Hartree−fock Based Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These end goals of these Quantum Communication sessions will be delivered to the boundary solution in a five-dimensional Chern-Simons supergravity application layer. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] In this effort, I propose QFT to QM Maximally Entangled States to achieve very high accuracy levels as say of the position and momentum, and spin and polarization projections which are represented in this Quantum Homeopathy paradigm, by Hermitian operators for the generation of Quantum Hormetic designed molecules of the Roccustyrna_gs, the Roccustyrna_fr, the Roccustyrna_gs_consv, and the Gissitorviffirna_TM ligands. The biological essence of this scheme is illustrated here by Quantum formalization of Quantum fields Theory (QFT) Uncertainities and Topology Geometric Methods in a Functional Quantum Negative Space for FH0∆ holomorphic functions for the generation of novel drug designs and theirs generalized k-nearest neighbors within this Quantum Homeopathy computing chemical context targeted in a atomistic level the (S) Spike proteins and its aspartic acid (SD614) and glycine (SG614) protein apparatus.…”
Section: Divide-and-conquer Approach For Hartree−fock Based Calculationsmentioning
confidence: 99%
“…Entanglement could be described here by the global variable 'no substance present' and the local variable "drug design" that the remedy is really translated to as if it was a remedy with 'something' in it and as another way of reconstructing chemical geometrics which would be that of a global variable 'specific remedy with no substance present' and the local variable 'chemical geometry shapes'. [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] Given the breadth of this mathematical geometry applications for Turing Machine learning approaches in biology, Ι focus my discussion below on these types of Quantum Homeopathy advantages and their potential applications in lieu of specific drug designing methods. Improvements to training landscapes that refer to the reduction or removal of barren plateaus and narrow gorges in the landscape of the objective function of a gradient-based learning algorithm may stem from the unitary property of (many) quantum circuits, which inherently maintain the length of the input feature vector throughout the computation 180] provided where an appropriate input encoding is used following a more dedicated, more precise, and more time-and energy-consuming interpretation of homeopathy remedies.…”
Section: Only These Entanglement Functions Of Chebyshevu[cosmentioning
confidence: 99%
“…At this stage of quantum biology studies, there are only mathematical models that would provide a new theory on ion channels functioning and related mechanisms of actions. Recent theoretical models [64,66,67] have suggested that different factors like hypoxia or inflammation implicated in the pathogenesis of excitability disorders, such as cardiac arrhythmias, epilepsy, and chronic pain disorders, can decrease the energy of the ion channel gate. In their calculations, authors showed that the gate-energy decrease caused by such factors can significantly augment the quantum tunneling to the degree that sodium, potassium ions, and protons will be able to depolarize the resting membrane potential.…”
Section: Ion Channels Dysfunction and Inherited Cardiac Diseasesmentioning
confidence: 99%
“…Additionally, the model of quantum tunneling has been applied on protons during acidosis and its related pathologies [66]. The mathematical calculations have shown that protons quantum tunneling through the closed sodium channels can depolarize the membrane potential, hence, cardiac arrhythmias or even cardiac arrest could happen.…”
Section: Ion Channels Dysfunction and Inherited Cardiac Diseasesmentioning
confidence: 99%
See 1 more Smart Citation